Meeting report: MyoIN – Pan-India collaborative network for myositis research - Latika Gupta; Sravan Kumar Appani; Ramya Janardana; Hafis Muhammed; Able Lawrence; Sanjiv Amin; Vineeta Shobha; Liza Rajasekhar; Ramnath Misra (Indian Journal of Rheumatology)
Rheumatology in India, albeit old, has lagged behind in research on epidemiology and outcomes of chronic rheumatic diseases. The realization about paucity of Indian data has created the felt need for cohort-building and sustainable research. With this comes the dawn of collaborative research. Myositis is one such rare disease with considerable morbidity and mortality, where little is known about the behavior of the disease and treatment practices in the Indian setting. In recent years with the availability of myositis-specific autoantibodies, newer clinic-serologic associations have been described. Collaborative efforts in rare diseases from the Western world have yielded exemplary results. Hence, a pan-India collaborative network called MyoIN (Myositis India Collaborative Effort) was formed to collect data on patients with inflammatory myositis in a standardized format including clinical and investigational parameters both at presentation and follow up to build up a large series prospectively. This report describes the activities since the inception of this group.